Circular RNA TGFBR2 acts as a ceRNA to suppress nasopharyngeal carcinoma progression by sponging miR-107. (28th February 2021) - Li, Wanpeng; Lu, Hanyu; Wang, Huan; Ning, Xianhui; Liu, Quan; Zhang, Huankang; Liu, Zhuofu; Wang, Jingjing; Zhao, Weidong; Gu, Yurong; Li, Houyong; Sun, Xicai; et al.
Abstract: Circular RNAs (circRNAs) act as competing endogenous RNAs, which are involved in the regulation of many types of cancers. They primarily function by sponging microRNAs (miRNAs) and influencing the expression of miRNA by target messenger RNA. However, the role of circRNAs in the progression of nasopharyngeal carcinoma (NPC) remains largely unclear. In this study, differentially expressed miRNAs associated with NPC were screened using microarray analyses, from which miR-107 was identified. Increased miR-107 expression was associated with poor prognosis in NPC, and miR-107 promoted the proliferation and migration of NPC cells. TGFBR2 was identified as the direct target of miR-107, which could reverse its effect on NPC cells. Furthermore, the expression of circTGFBR2 was downregulated in NPC tissue samples, while circTGFBR2 overexpression correlated with favorable prognosis in NPC. Functionally, circTGFBR2 overexpression inhibited the proliferation and migration of NPC cells both in vitro and in vivo. Further analysis showed that circTGFBR2 sponged miR-107, leading to the upregulation of TGFBR2 expression and suppression of NPC progression. Therefore, circTGFBR2 may serve as a novel tumor suppressive factor and potential target for new therapies in NPC patients. Highlights: The expression of circTGFBR2 is downregulated in NPC tissue samples. circTGFBR2 overexpression is correlated with favorable prognosis in NPC. circTGFBR2 suppresses the proliferation and migration of NPC both in vitro and in vivo. circTGFBR2 suppresses nasopharyngeal carcinoma progression through miR-107/TGFBR2 axis. circTGFBR2 may be a promising diagnosis biomarker and a therapeutic target in NPC.